1996
DOI: 10.1074/jbc.271.12.6866
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the Second Largest Subunit of RNA Polymerase II Cause 6-Azauracil Sensitivity in Yeast and Increased Transcriptional Arrest in Vitro

Abstract: Yeast RNA polymerase II enzymes containing single amino acid substitutions in the second largest subunit were analyzed in vitro for elongation-related defects. Mutants were chosen for analysis based on their ability to render yeast cells sensitive to growth on medium containing 6-azauracil. RNA polymerase II purified from three different 6-azauracil-sensitive yeast strains displayed increased arrest at well characterized arrest sites in vitro. The extent of this defect did not correlate with sensitivity to gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
97
0
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(101 citation statements)
references
References 55 publications
(57 reference statements)
2
97
0
2
Order By: Relevance
“…Previous systematic pharmacogenetic screens had revealed that htz1⌬ single mutants have decreased resistance to 6-azauracil and mycophenolic acid (MPA) (17,82). By inhibiting inosine 5Ј-monophosphate (IMP) dehydrogenase, both of these drugs decrease the pool of ribonucleotides in vivo, which is not well tolerated in mutants with known defects in transcription elongation (21,35,61,64,76). Thus, the hypersensitivity of the single htz1⌬ mutant to these agents is potentially strong evidence for a role in elongation.…”
Section: Resultsmentioning
confidence: 99%
“…Previous systematic pharmacogenetic screens had revealed that htz1⌬ single mutants have decreased resistance to 6-azauracil and mycophenolic acid (MPA) (17,82). By inhibiting inosine 5Ј-monophosphate (IMP) dehydrogenase, both of these drugs decrease the pool of ribonucleotides in vivo, which is not well tolerated in mutants with known defects in transcription elongation (21,35,61,64,76). Thus, the hypersensitivity of the single htz1⌬ mutant to these agents is potentially strong evidence for a role in elongation.…”
Section: Resultsmentioning
confidence: 99%
“…Frequently, elongation factor mutants are hypersensitive to 6-AU, presumably because they are less tolerant to 6-AU-induced pausing. An rpb2-7 mutant is strongly sensitive to 6-AU but shows phenotypes distinct from rpb1-221 and rpb2-10 (74,76,77). Fig.…”
Section: B-d)mentioning
confidence: 90%
“…These gaps likely reflect sites of paused complexes. Increased susceptibility to pausing/arresting has been shown to correlate with slower elongation rates (36).…”
Section: Polymerase-free Gaps Are More Frequently Observed In Ctr9⌬ Cmentioning
confidence: 99%